Childhood Disorder: Dysregulated Self-Conscious Emotions? Psychopathological Correlates of Implicit and Explicit Shame and Guilt in Clinical and Non-clinical Children and Adolescents - Hendriks, Eline; Muris, Peter; Meesters, Cor; Houben, Katrijn (Frontiers in Psychology, 2022)
This study examined psychopathological correlates of implicit and explicit shame and guilt in clinical and non-clinical youths aged 8 to 17 years. Shame and guilt were measured explicitly via two self-reports and a parent report, and implicitly by means of an Implicit Association Test (IAT), while a wide range of psychopathological symptoms were assessed with questionnaires completed by children, parents, and teachers. The results showed no differences of implicit and explicit shame and guilt between the clinical and non-clinical group, implying that dysregulation of these self-conscious emotions is not per definition associated with psychopathology. Correlational analyses indicated that self-reported explicit shame was positively associated with a broad range of internalizing psychopathology, while self-reported explicit guilt was associated with higher levels of anxiety and to some extent lower levels of externalizing psychopathology. Correlations with parent-rated shame and guilt revealed the same pattern of results but were in general weaker. Furthermore, implicit shame and guilt did not show significant correlations with the various measures of psychopathology. It can be concluded that the link between shame and guilt and psychopathology is complex, and partly dependent on the disorder under study and context-related factors defining the maladaptive nature of these self-conscious emotions.